MONITORING KEPATUHAN NEGARA PESERTA KONVENSI PENGUNGSI MELALUI SISTEM MONITORING HAM INTERNASIONAL - Ilham Aji Pangestu; Irma Sri Rejeki (Universitas Islam Syekh Yusuf, 2022)
This study aims to find out how to monitor the compliance of countries participating in the convention through an international human rights monitoring system. This research is a normative legal research. The approaches used in this research include the statutory approach and the case approach, which are obtained from legal materials conducted through a literature study. Based on research, it is known that there is no monitoring system for state compliance with a convention, in this case the refugee convention. Reservations in conventions are often excluded on grounds of State ownership. On the other hand, refugees themselves have the same human rights as other human rights. International human rights monitoring mechanisms consist of treaty-based mechanisms and charter-based mechanisms. The international human rights monitoring system is the one most closely related to the supervision of participating countries/monitoring of the 1951 Convention considering the system between refugees and the human rights attached to it. In this case, the international human rights monitoring mechanism that can be used is a mechanism based on a treaty or a mechanism based on an international agreement. Keywords: Refugee Monitoring; Internasional Human Right Mnitoring; Refugee Convention